«Go away from Moscow…». Mykola Khvylovy – destroyer of imperial myths (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
The article analyzes the pamphlets by Mykola Khvylovy who declaring the slogan «go away from Moscow» and resorted to the destruction of imperial myths about the cultural and linguistic Russian superiority. The literary debate went beyond purely artistic. The artist's pamphlets turned into political ideas, in which there was a place not only for cultural independence, but also for the state. Texts that have seen the world from 1925 to 1928 years raise the annoying issues of Russification and the needs of the state of Ukraine cultural landmarks of Ukrainian youth, which is the call to abandon Russian literature and focus on «psychological Europe». Mykola Khvylovy countered the Ukrainian colonial adaptation («flunky declining») with a total sense of freedom. Pamphletes Mikola Khvylovy to ruynuvan vcorea in ukraïnsku awareness MFW about rosiyska kulturno th movo visct. Vambraces from the Russian lterature, apelu to Evropeiskogo dowu on runah: cultural, stolichnomu, social. Lterature debate vihodit for me. Unfortunately, the story of the destruction of the myth had a tragic ending. Mykola Khvylovy's repentant speeches eventually hurt him. He is increasingly showing an ambiguous stance, thereby underscoring the value of pamphlets, although he is also aware that the empire will not dispense with "little blood" and will require a more radical demonstration of humility. In this absurdly tragic situation, the artist chooses the only possible solution – suicide. t is noted that in the context of the language issue, the writer also raises the problem of translations into Ukrainian. He deconstructs the myth that, on the one hand, only the Russian language is suitable for translation, on the other - that Ukrainians are not able to make a quality translation into the national language.
Keywords: pamphlet; imperial myth; psychological Europe; messianism; Asian Renaissance